Prospective bacterial quorum sensing inhibitors from Indian medicinal plant extracts. (1st July 2017) - Tiwary, B.K.; Ghosh, R.; Moktan, S.; Ranjan, V.K.; Dey, P.; Choudhury, D.; Dutta, S.; Deb, D.; Das, A.P.; Chakraborty, R.
Abstract: As virulence of many pathogenic bacteria is regulated by the phenomenon of quorum sensing (QS), the present study aimed to find the QS‐inhibiting (QS‐I) property (if any) in 61 Indian medicinal plants. The presence of QS‐I compound in the leaf extract was evaluated by its ability to inhibit production of pigment in Chromobacterium violaceum MTCC 2656 (violacein) and Pseudomonas aeruginosa MTCC 2297 (pyocyanin) or swarming of P. aeruginosa MTCC 2297. Extracts of three plants, Astilbe rivularis, Fragaria nubicola and Osbeckia nepalensis, have shown a dose‐dependent inhibition of violacein production with no negative effect on bacterial growth. Inhibition of pyocyanin pigment production and swarming motility in P. aeruginosa MTCC 2297 was also shown. Based on the results obtained by gas chromatography–mass spectroscopy (GC‐MS) and thin‐layer chromatography–direct bioautography (TLC‐DB), it was concluded that triterpenes and flavonoid compounds found in the three plant extracts could have QS‐I activity. Significance and Impact of the Study: A novel alternative prospect to prevent bacterial infections without inhibiting the growth is to apply chemicals that inhibit quorum sensing mechanism of the pathogens. Antiquorum property of 61 medicinal plants was evaluated by the ability of their leaf extract(s) to inhibit production of pigment (violacein in Chromobacterium violaceum MTCC 2656, pyocyanin in Pseudomonas aeruginosa MTCC 2297) or swarming in P. aeruginosa MTCC 2297. The most prospective plants (for the development of quorum sensing inhibitor), showing inhibition of violacein production without affecting bacterial growth, were Astilbe rivularis, Fragaria nubicola and Osbeckia nepalensis .